PENGARUH PENGGUNAAN MEDIA VIDEO TUTORIAL TERHADAP HASIL BELAJAR SENI RUPA SISWA KELAS X DI SMA NEGERI 1 SAWAHLUNTO - FULKHA TAJRI M, Dr. Ramalis Hakin, M.Pd., Yofita sandra, S.Pd., M.Pd. (Serupa The Journal of Art Education, 2017)
The purpose of this thorough to understand that there is an influence of using tutorial video media to the result of art and culture in art lesson at grade X in Senior High School 1 Sawahlunto. The kind of thorough that used is experiment by interpretation score of pre-test and pos-test and then by technique interpretation encode for processing Purposive Sampling. This encode for processing collected by the test in the result of lesson. Finding in this thorough showing that : the result of student’s in the lesson by using tutorial video media is better, just than with students who teached without using a simple media. That’s mean using tutorial video media needed to all of students for improving the result of students in the lesson specially for art and culture lesson in art at Senior High School 1 Sawahlunto.Keywords: Tutorial Video Media